Opacités et implicites : ce que Parcoursup fait au groupe professionnel des enseignant·es - Alexie Geers; Florence Legendre; Samuel Pinto (Éducation et Socialisation)
We propose to understand the effects of the recent reforms related to the orientation process, including Parcoursup, on division of labor in the school world and, in particular on the professional group of high school teachers. Our analysis is based on socio-ethnographic research conducted in an high school. The multiple and nebulous prescriptions redefine the license and mandate (Hughes, 1996) of teachers by broadening their field of action opaquely. These new modes of regulation challenge the boundaries and jurisdictions (Abbott, 2016) of their work. To shed light on the opacities of the system, they resort to pedagogical DIY. Their commitments vary according to their social and professional dispositions and the students' academic profiles.